ABDICATION OF THE SOVEREIGN SELF the psycholinguistics of invalid synthetic ... propositions. (CAMBRIDGE SCHOLARS PUBLIS, 2018)
Language and logic are inextricably commingled in our everyday speech. What we say, particularly in the form of statements, tends not only to mirror our world, but mold it into our own image. This book looks at how much of our verbal communication can be considered ""valid"" from the point of view of the rules of logic. Are we saying what we mean to say? Is what we hear from the media, our peers, our leaders, and those who determine the narrative ""story"" of our lives meaningful, rational, and logical? Even more important than the answers to these questions is the answer to whether we are the.